A study of the thought of selected muslim intellectuals in Iran on islam and modernity, with special reference to science and politics / Maryam Shamsaei - Shamsaei, Maryam (2012)
Nothing troubled the people of the Islamic world at the beginning of the twenty-first century as much as the challenge of modernity did. It had occupied a central place in the cultural and sociopolitical agendas of intellectual and social movements, and state actors in the Islamic world and Iran since the 19th century. This study is a theoretical analysis of Iranian Muslim intellectuals’ encounter with Islam and modernity. The two main spheres of modernity which are examined are: i) the political arena and the government structure, and ii) science and technology. The goal of this dissertation is to examine and investigate the controversial ideas of five Iranian Muslim intellectuals, namely: Ali Shariati, Abdolkarim Soroush, Seyyed Hossein Nasr, Murteza Mutahhari, and Mehdi Golshani. Their ideas were then compared in order to identify the similarities and dissimilarities in their ideas on Islam and modernity. It is hoped that through this study, a contribution can be made to the current debate on Islam, science and politics, as well as creating an alternative Islamic perspective with regards to science, technology and a systematic government. This study is part of an accumulated effort towards the rejuvenation of the Islamic world in the modern era, including the field of science and technology. The religious thinkers have taken either of the following two major positions in viewing modernisation: (a) In support of selective modernisation, (b) In opposition to selective modernisation. The supporters of selective modernization are mostly concerned about the development and the survival of the developing countries and civilizations and the opponents have traditional Islamic culture in mind. We can therefore take the middle line and consider a middle point in this argument; meaning to suggest that instant development and survival is helpful and effective, but genuine, sustainable development requires patience and adherence to Islamic principles. Therefore the adherence of Islamic nations to the notions of modernity is just a result of the concern for survival, rather than true human development. In its true sense a move toward a real Islamic ruling and Islamic democracy is in fact the basis for an optimal path to development. Based on this reality, and considering that it is necessary to survive in this world, we have to accept modernisation to the extent which is necessary. On the other hand and based on the idea of selective modernisation, we have to aim at reviving the real Islamic nation when working toward development.